Progress and perspectives of perioperative immunotherapy in non-small cell lung cancer - Peng, Yurong; Li, Zhuo; Fu, Yucheng; Pan, Yue; Zeng, Yue; Liu, Junqi; Xiao, Chaoyue; Zhang, Yingzhe; Su, Yahui; Li, Guoqing; Wu, Fang (Frontiers in Oncology, 2023)
Lung cancer is one of the leading causes of cancer-related death. In recent decade, its mortality has decreased partly attributed to updated therapy. Curative surgery for patients with lung cancer at an early stage is the standard of care, but not all the surgical prognosis showing good results. To improve the prognosis of patients with resectable lung cancer, adjuvant and neoadjuvant chemotherapy as the perioperative treatment have currently been used, indeed achieving better outcomes. Immunotherapy, as an epoch-making treatment, has improved the curative effect and prognosis and increased tolerability compared with traditional and ordinary cytotoxic chemotherapy of malignant tumors, giving new hope for patients with NSCLC. Meanwhile, different immunotherapy-related clinical trials have achieved encouraging clinical outcomes, and there explored different modes of perioperative immunotherapy, from neoadjuvant immune checkpoint inhibitors (ICIs) monotherapy, neoadjuvant immune-combination therapy (chemoimmunotherapy, immunotherapy plus antiangiogenic therapy, immunotherapy plus radiotherapy or concurrent chemoradiotherapy) to adjuvant immunotherapy and neoadjuvant combined adjuvant immunotherapy. Recently, phase 3 studies like the IMpower 010 and the CheckMate 816 research showed advances in perioperative immunotherapy treatments and led to survival benefits for operable patients. In this review, we are supposed to summarize up-to-date clinical studies, analyze efficiency and feasibility of different neoadjuvant therapies, biomarkers for neoadjuvant immunotherapy and to find the optimal mode of perioperative immunotherapy for NSCLC.